2006
DOI: 10.1253/circj.70.37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraaortic Balloon Pumping on the Angiographic No-Reflow Phenomenon After Percutaneous Coronary Intervention in Patients With Anterior Myocardial Infarction

Abstract: ntraaortic balloon pumping (IABP) is widely used in patients with cardiogenic shock, as well as in many other situations such as support for high risk angioplasty, refractory congestive heart failure, and post-myocardial infarction unstable angina. 1 The effects of IABP are considered to be a reduction in myocardial oxygen demand because of systolic left ventricular (LV) unloading and an increase in coronary blood flow. Although the former effect is well recognized, the latter effect remains controversial, 2-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…5,24,25 The aforementioned pathophysiological mechanism is supported by the fact that in our study we observed a significant positive correlation both between afterload and infarcted area (Figure 5B) and between infarcted area and NR area (Figure 5C). Taking the above into consideration, it is conceivable that interventions that increase reperfusion pressure and myocardial blood flow but concurrently decrease left ventricular afterload and myocardial oxygen consumption (like the intra-aortic balloon pump) 26,27 may result in attenuation of the NR phenomenon. 28,29 Second, increased afterload may directly affect NR, irrespective of changes in infarct size; elevations in blood pressure may result in increased resistance of the microvascular bed, due to higher extravascular resistive forces resulting from elevated left ventricular pressures (which increase in parallel with the aortic pressure).…”
Section: Discussionmentioning
confidence: 99%
“…5,24,25 The aforementioned pathophysiological mechanism is supported by the fact that in our study we observed a significant positive correlation both between afterload and infarcted area (Figure 5B) and between infarcted area and NR area (Figure 5C). Taking the above into consideration, it is conceivable that interventions that increase reperfusion pressure and myocardial blood flow but concurrently decrease left ventricular afterload and myocardial oxygen consumption (like the intra-aortic balloon pump) 26,27 may result in attenuation of the NR phenomenon. 28,29 Second, increased afterload may directly affect NR, irrespective of changes in infarct size; elevations in blood pressure may result in increased resistance of the microvascular bed, due to higher extravascular resistive forces resulting from elevated left ventricular pressures (which increase in parallel with the aortic pressure).…”
Section: Discussionmentioning
confidence: 99%
“…129,130 Inadequate therapies Intra-aortic balloon pumping (IABP) is able to reduce myocardial oxygen demand due to systolic left ventricular unloading and increases myocardial perfusion. 131,132 However, Maekawa et al failed to show an increase of mean diastolic flow velocity and peak diastolic flow velocity in left anterior descending by IABP in patients with angiographic CMVO. 131 Moreover, IABP failed to reduce IS in high-risk PCI.…”
Section: Controversial Therapiesmentioning
confidence: 99%
“…131,132 However, Maekawa et al failed to show an increase of mean diastolic flow velocity and peak diastolic flow velocity in left anterior descending by IABP in patients with angiographic CMVO. 131 Moreover, IABP failed to reduce IS in high-risk PCI. 132…”
Section: Controversial Therapiesmentioning
confidence: 99%
“…In addition, it has been reported that distal protection devices are considered to be effective in preventing distal embolization, particularly in animal experimental studies [16]. A common practice is to use intra-aortic balloon pump (IABP) in patients with the no reflow phenomenon with the expectation of an increase in diastolic coronary flow and improved cardiac function [17]. The phenomenon is closely related to the clinical outcome of patients, and is one of the leading causes of death after PCI [18].…”
Section: Introductionmentioning
confidence: 99%